2021
DOI: 10.1097/ta.0000000000003120
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prehospital TXA on mortality among bleeding trauma patients: A systematic review and meta-analysis

Abstract: BACKGROUND:Tranexamic acid (TXA) is an antifibrinolytic drug associated with improved survival among trauma patients with hemorrhage.Tranexamic acid is considered a primary hemostatic intervention in prehospital for treatment of bleeding alongside blood product transfusion. METHODS:A systematic review and meta-analysis was conducted to investigate the impact of prehospital TXA on mortality among trauma patients with bleeding. A systematic search was conducted using the National Institute for Health and Care Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Early in-hospital mortality (after 6 h und 12 h) was significantly lower in the TXA group with a respective trend for the first 24 h after admission [ 34 ]. Death due to trauma associated hemorrhage was significantly less common.…”
Section: Discussionmentioning
confidence: 99%
“…Early in-hospital mortality (after 6 h und 12 h) was significantly lower in the TXA group with a respective trend for the first 24 h after admission [ 34 ]. Death due to trauma associated hemorrhage was significantly less common.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of benefit to early administration of TXA has led to the growing implementation of prehospital TXA to injured patients at risk of bleeding [1,7,12,13,18,[46][47][48][49][50][51][52]. An earlier retrospective study from our center demonstrated that prehospital TXA administration was associated with a lesser need of in-hospital blood transfusion and MTP activation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic injuries represent 10% of the disease burden worldwide and particularly trauma-induced hemorrhage which is the most preventable cause of mortality among injured patients [1][2][3][4]. Around one-fourth of trauma patients are susceptible to develop acute coagulopathy and those with uncontrolled hemorrhage are at increased risk of hemorrhagic shock and mortality [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery. [11][12][13][14] As a synthetic lysine analogue, TXA can modify brain network excitability by activating excitatory ionotropic glutamate receptors. 15 16 On the other hand, TXA may induce hyperexcitability by blocking gamma-aminobutyric acid-driven inhibition of the central nervous system.…”
Section: Open Accessmentioning
confidence: 99%
“…TXA is used as a bolus ranging from 10 to 50 mg/kg, followed by a continuous infusion ranging from 1 to 5 mg/kg/hour until the end of the procedures in a variety of neurosurgical procedures 3 8–10. Unfortunately, the risk of postoperative seizures remains uncertain, and restricts the routine use of TXA in neurosurgery, though it is a safe and effective means to reduce operative blood loss and blood transfusion rates in cardiac, pulmonary, trauma, obstetric, spinal and orthopaedic surgery 11–14…”
Section: Introductionmentioning
confidence: 99%